(untitled) (Research, Society and Development, 2021)
Worldwide, gold amalgamation is conventionally done using mercury. However, the pollution resulting from the use of mercury is of the most concern, as it has devastating effects on human health and the environment. This work addresses the evaluation of the effectiveness of the application of Ochroma pyramidale leaves to support the gravity concentration of gold in the Alto Revuè sub-basin, in the district of Manica, in the extreme center-west of the province of Manica, in the center of Mozambique. The work was essentially based on bibliographical and documental research and on testing the process of supporting the gravity concentration of gold using the leaves of the plant. 10 tests were carried out using the leaf of this plant, in which 251 miners participated. From the tests carried out, it was observed that the leaves of Ochroma pyramidale proved to be able to lighten and separate the gold from other materials only in areas where the dimensions of the gold particles were relatively larger. However, there are studies that prove that Manhiot esculenta Grantz (bitter cassava) is effective in supporting the gravity concentration of gold, attracting gold particles, which marks the beginning of a very promising future in mining because bitter cassava can already be used, replacing the mercury. Therefore, it is recommended to carry out pilot work for demonstrating the use of bitter cassava.